Stem cell therapies and glioma stem cells in glioblastoma: a systematic review of current challenges and research directions - Olivier Uwishema; Sanobar Shariff; Magda Wojtara; Judy Ahmad El Chakik; Shankhaneel Ghosh; Kehinde Obamiro; Syed Ather Enam (International Journal of Emergency Medicine)
Abstract Background Glioblastoma is the most aggressive tumor of glial origin and the most common, as established by the World Health Organization. GBM has been one of the most intractable tumors with minimal progress in prognosis despite decades of research. Stem cell therapy (SCT) has raised hopes with regard to possibly targeting tumor progression and recurrence. Glioma stem cells (GSCs) are directly involved in gliomagenesis and chemoresistance, thus constituting potential valuable therapeutic targets for improving treatment outcomes. Objective The objective of this review article is to assess and consider the potential therapeutic benefits, challenges, and prospective research directions for SCTs for glioblastoma with a particular focus on GSCs as key therapeutic targets. Materials and methods A literature review was performed using search terms and Boolean operators pertinent to SCT and glioblastomas to gather all existing literature. The databases PubMed/MEDLINE, Scopus, and the Cochrane Library were searched in accordance with the standard guidelines of Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) 2020. Results and conclusions The review established that the main mesenchymal stem cells (MSCs), neural stem cells (NSCs), induced pluripotent stem cells (iPSCs), and hematopoietic stem cells are the first SCTs evaluated in terms of their potential as a glioblastoma therapy. While SCTs were found to be effective in tumor targeting and immune modulation, they face certain restrictions, including death of stem cells inside the body, tumor heterogeneity, and transformation to malignancy. Research must now focus on the combination of stem cell therapy with molecular-targeted therapy and advanced delivery systems for improved tumor targeting, better overcoming resistance, and enhancing both efficacy and safety for patients undergoing treatment for glioblastoma.